Uganda : How Long Do the Effects of Cash Grants Last? - World Bank (World Bank, Washington, DC, 2019)
Training vouchers and microfinance tools are often used by multilateral organizations, non-governmental organizations, and governments to increase employment and business oppor¬tunities in low- and middle-income countries. An alternative is putting cash directly in the hands of the poor themselves, leaving them to decide how best to use the money for income-generating activities. One of the assumptions underlying these programs is that poor people can generate high returns to capi¬tal but often have trouble saving money and accessing credit. Giving people cash enables them to bypass these obstacles to starting or improving a business. Recent studies have found that simply giving people cash can improve incomes, at least in the first few years, and the cash is very rarely squandered or misused. However, very little is known about the effectiveness of start-up grants in the long run.